Penerapan Metode AHP-WP Dalam Penentuan Lulusan Terbaik Profesi Ners UMKT - Fajrul Pallah, Bintang; Latipah, Asslia Johar; Rahim, Abdul (Jurnal Tika, 2023)
The Ners profession is an advanced study program in the field of nursing. In completing their studies, the best graduate students will be selected. In the implementation of determining the best graduates, there are several criteria that must be met, but in its implementation it still uses certain criteria that are not objective. Therefore, a decision-making method is needed that can take into account all the criteria used to determine the best graduates. Based on the criteria that have been determined by the UMKT Nursing Profession Study Program, calculations are carried out using the AHP-WP method. The AHP method is used to determine the weight of each criterion, while the WP method is used for ranking alternatives. From the results of the calculation it can be that alternative 1 (Dinda Ayu Framaisella) as rank 1 which means being the best graduate. In this test, an accuracy of 73.40% was obtained using 94 alternative data from Nursing Profession students for the 2021/2022 academic year.